Multibrand, multisystem and multirole franchising: A qualitative exploration and framework development in Brazil. (4th March 2022) - Grünhagen, Marko; González-Díaz, Manuel; Hussain, Dildar; Monteiro da Silva Filho, Haroldo
ABSTRACT: We investigate franchisees' rationales for ownership constellations beyond single brands or systems. Through exploratory interviews with Brazilian franchisees, reasoning and process of how franchisees develop their multibrand, multisystem and multirole portfolio is elucidated. Franchisees in Brazil with ownership stakes in more than one brand/system aim to keep units within their monitoring range, while diversifying to mitigate risk of their portfolios. Brazilian franchisees have created an active marketplace in which franchises are traded akin to commodities and franchises serve as schools or entrepreneurial "internships" for franchisees who seek new skills. A new framework of laddered diversification options in franchising is developed.